2022
DOI: 10.1186/s13287-022-02736-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequential transplantation of exosomes and mesenchymal stem cells pretreated with a combination of hypoxia and Tongxinluo efficiently facilitates cardiac repair

Abstract: Background Bone marrow-derived mesenchymal stem cells (MSCs), which possess immunomodulatory characteristic, are promising candidates for the treatment of acute myocardial infarction (AMI). However, the low retention and survival rate of MSCs in the ischemic heart limit their therapeutic efficacy. Strategies either modifying MSCs or alleviating the inflammatory environment, which facilitates the recruitment and survival of the engrafted MSCs, may solve the problem. Thus, we aimed to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 68 publications
(92 reference statements)
0
15
0
Order By: Relevance
“…There were large amounts of studies that investigated exosomes derived from mesenchymal stem cells, such exosomes exhibited protective effects in cardiac injury and many miRNAs were reported to be encapsulated in exosome cargo. Especially, exosomes derived from hypoxia pretreated bone marrow-derived mesenchymal stem cells (BMSCs) were able to improve the cardiac function, reduce the infarct size and enhance the angiogenesis of the infarcted hearts ( 141 ). miR-98-5p was upregulated by hypoxia in exosomes derived from BMSCs and injection of such exosomes to rats with myocardial ischemia-reperfusion injury improved the cardiac function by targeting TRL4 and activating PI3K/AKT signaling pathway ( 149 ).…”
Section: Hypoxic Exosomes In Cardiologymentioning
confidence: 99%
“…There were large amounts of studies that investigated exosomes derived from mesenchymal stem cells, such exosomes exhibited protective effects in cardiac injury and many miRNAs were reported to be encapsulated in exosome cargo. Especially, exosomes derived from hypoxia pretreated bone marrow-derived mesenchymal stem cells (BMSCs) were able to improve the cardiac function, reduce the infarct size and enhance the angiogenesis of the infarcted hearts ( 141 ). miR-98-5p was upregulated by hypoxia in exosomes derived from BMSCs and injection of such exosomes to rats with myocardial ischemia-reperfusion injury improved the cardiac function by targeting TRL4 and activating PI3K/AKT signaling pathway ( 149 ).…”
Section: Hypoxic Exosomes In Cardiologymentioning
confidence: 99%
“…However, the harsh microenvironments, such as calcium overload, acidosis, and reactive oxygen species production in the injured myocardium, significantly dampen the survival rate of the transplanted exosomes and undermine the incidence of homing to the injured tissue, posing great limits on their clinical application as cell-free therapies ( 34 ). The injection of exosomes into myocardial tissue at the early stage of MI can effectively reduce inflammation, inhibit apoptosis, and increase SDF-1 expression ( 35 ). Additionally, pre-hypoxic treatment of stem cell-derived exosomes in cardiomyocytes can significantly promote angiogenesis, reduce cardiac fibrosis, and improve cardiac function ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of exogenous vesicles into the ischemic heart within 30 min of MI significantly modulates the ischemic environment, including decreasing inflammatory IL-6 and TNFα, enhancing SDF-1 expression and MSC survival. Additionally, several studies have demonstrated that combined pretreatment with hypoxia and the herbal compound Tongxinluo can effectively achieve better performance in facilitating cardiac repair through increasing CXCR4 expression, which provides new insights into stem cell therapy for cardiac rehabilitation (Xiong et al, 2022). Furthermore, Ruan et al suggested that Suxiao Jiuxin pills modulate myocardial MSC-Exos, causing structural genetic chromatin remodeling in recipient cardiomyocytes and accelerating cardiomyocyte propagation (Ruan et al, 2018).…”
Section: Drug Pretreatment Of Extracellular Vesicles To Enhance Its T...mentioning
confidence: 99%